THE DEVELOPMENT STRATEGY OF THE REGIONAL FISHERY PORT I CAROCOK TARUSAN IN WEST SUMATRA PROVINCE IN IMPLEMENTING THE FUNCTION OF A FISHERY PORT - Putri Wangi Tri Rumelia; Jonny Zain; Polaris Nasution (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This research was conducted in October and November 2022. The research aims to identify problems in the implementation of fisheries port functions in the Regional Fishery Port I Carocok Tarusan and to find solutions in the form of strategies that must be implemented so that the Regional Fishery Port I Carocok Tarusan can apply all fisheries port functions in accordance with Ministerial Regulation No. 08/MEN/2012. The method used is a survey method. The data collected in this research relate to the implementation of fisheries port functions under Ministerial Regulation No. 08 of 2012 at the Regional Fishery Port I Carocok Tarusan. Data analysis was carried out descriptively by examining the conformity of the functions of the Regional Fishery Port I Carocok Tarusan with Ministerial Regulation No. 08 of 2012. Furthermore, a SWOT analysis was conducted to identify strategies to implement so that these functions can be carried out at the Regional Fishery Port I Carocok Tarusan. The results of the study indicate that out of the 9 functions that have been established, only a few functions have been implemented by Regional Fishery Port I Carocok Tarusan, including the function of providing services for mooring and anchoring of fishing boats, the function of fish loading and unloading services, the function of fish marketing and distribution, the function of providing logistics and supplies for fishing vessels, the function of marine tourism, and the function of providing and/or other services in accordance with the applicable laws and regulations. The results of the SWOT analysis show that the position of Regional Fishery Port I Carocok Tarusan is in quadrant III; therefore, a turnaround W-O (Weaknesses-Opportunities) strategy is needed to minimize weaknesses and take advantage of opportunities